A rare case scenario of didelphic uterus with ovarian serous cystadenocarcinoma: an unusual clinical finding - Sharma, Medhavi; Sharma, Gaurav; Varshney, Shivangi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Uterine didelphys in women is uncommon. The improper development of the Mullerian ducts during the intrauterine period leads to congenital abnormalities of the female genital system. Mullerian duct canalization or improper fusion leads to a didelphic uterus. About 60% of ovarian neoplasms are epithelial in origin, and the surface epithelium is typically most affected. This case report describes the management of a patient who had previously undergone two caesarean sections for a rare gynecological case of didelphic uterus with unilateral serous cystadenocarcinoma of the ovary.